2008
DOI: 10.1529/biophysj.108.141275
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Temperature on Mechanical Resistance of the Native and Intermediate States of I27

Abstract: We investigated the effect of temperature on the mechanical unfolding of I27 from human cardiac titin, employing a custom-built temperature control device for single-molecule atomic force microscopy measurement. A sawtooth pattern was observed in the force curves where each force peak reports on the unfolding of an I27 domain. In early unfolding events, we observed a "hump-like" deviation due to the detachment of beta-strand A from each I27 domain. The force at which the humps appear was approximately 130 pN a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
42
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 50 publications
11
42
2
1
Order By: Relevance
“…By extrapolating the unfolding rate in the absence of force for different temperatures, varying within the range 5-45°C, we measure a value for the activation barrier of ⌬G ‡ ϭ 71 Ϯ 5 kJ/mol and an exponential prefactor ‡ ϳ4 ϫ 10 9 s Ϫ1 . Contrary to the results reported for filamin (25), and similar to the case of the I27 protein (26), the major effect of temperature is to significantly lower the height of the energy barrier, whereas the distance to the transition state increases only slightly within the range of temperatures probed in our experiments. The measured value for the exponential prefactor for mechanical unfolding, ‡ , on the nanosecond timescale, places an upper limit to the diffusive mean first passage time for unfolding.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…By extrapolating the unfolding rate in the absence of force for different temperatures, varying within the range 5-45°C, we measure a value for the activation barrier of ⌬G ‡ ϭ 71 Ϯ 5 kJ/mol and an exponential prefactor ‡ ϳ4 ϫ 10 9 s Ϫ1 . Contrary to the results reported for filamin (25), and similar to the case of the I27 protein (26), the major effect of temperature is to significantly lower the height of the energy barrier, whereas the distance to the transition state increases only slightly within the range of temperatures probed in our experiments. The measured value for the exponential prefactor for mechanical unfolding, ‡ , on the nanosecond timescale, places an upper limit to the diffusive mean first passage time for unfolding.…”
contrasting
confidence: 99%
“…These studies have provided valuable information regard-ing their nanomechanical properties, which are intimately related to the structural topology. Previous single molecule mechanical studies have investigated the effect of temperature on the nanomechanical properties of proteins (23)(24)(25)(26)(27)(28). Qualitatively, these works reported an expected decrease in the mechanical stability of the protein as the temperature was increased.…”
mentioning
confidence: 99%
“…Traditionally, chemical denaturants such as guanidinium chloride and thermal perturbation along with spectroscopic methods have been used to study protein folding [9]. Recent studies have shown that it is important to combine single-molecule experiments with either chemical denaturants or with thermal perturbations to study folding processes [10][11][12][13][14]. They proposed that such combinations of multiple techniques along with comparisons of results from multiple probes are useful for validating the protocol used [12].…”
Section: Introductionmentioning
confidence: 99%
“…The protein was selected based on recent experimental studies of this protein [11,13], and the validity of the end-to-end distance as the order parameter for the unfolding of this protein. Botello et al showed that the free-energy barrier during the mechanical unfolding of I27 decreases linearly with respect to increasing temperature and the concentration of the chemical denaturant, guanidinium chloride [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation